(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
Emotions are essential to interpersonal relationships. The interaction among parents and children is vital in the learning of emotional management. The aim of this study was to analyze the reactions of mothers facing the emotional expressions of anger and sadness of their children. It was used a case study with 30 mothers, mean age 34.8 years old, belonging to social classes A to C and having two or more children aged between five to ten years old. Two open questions were applied to investigate a situation in which the child felt sadness and anger and two stimulus-stories based on literature to the same emotions were used. The interviews were recorded and transcribed. A quantitative and qualitative content analysis was carried out, which showed preponderant use of maladaptive strategies, especially for punishment and anger minimization as well as punishment and replacement for sadness. The reaction focused on the problem was indicated to the sadness when related to loss.